PEMETAAN KONFLIK DI TIMUR TENGAH: (Tinjauan Geografi Politik) - Nilna Indriana (AN-NAS, 2017)
“Middle East in all its complexity, has always been an area of ​​concern to humanity from time to time. So much history is engraved in this area, began its cultural golden stretches in the valley of the Nile, Euphrates and Tigris, until the major political forces of Iran with the birth of Islam were able to change the form of government of the Islamic Republic, until the blood battle in a variety of domestic political interests, regional and international level in various conflict situations; Arab-Israeli war, the US-invasion of Iraq until the political revolution "Arab Spring" in some Arab countries. Not only that, The Middle East is also a spiritual direction with the birth of the great religions of the world, whose influence was felt hundreds of millions of human beings until today. But ironically, The strategic location of the region with all the wonders that should make this a more stable, but otherwise This area is known as "Hot area" with conflicts of interest. From this condition, I am interested to analyze why the frequent conflicts in the Middle East and the factors that cause these conflicts.”